2007
DOI: 10.1007/s11104-007-9197-5
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous distribution of phosphorus and potassium in soil influences wheat growth and nutrient uptake

Abstract: Heterogeneous distribution of mineral nutrients in soil proWles is a norm in agricultural lands, but its inXuence on nutrient uptake and crop growth is poorly documented. In this study, we examined the eVects of varying phosphorus (P) and potassium (K) distribution on plant growth and nutrient uptake by wheat (Triticum aestivum L.) grown in a layered or split soil culture in glasshouse conditions. In the layered pot system the upper soil was supplied with P and either kept watered or allowed to dry or left P-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 37 publications
1
11
0
1
Order By: Relevance
“…The climate chamber experiment, where all other heterogeneities had been evened out by soil homogenization, confirmed that preferential allocation of root growth is indeed a response of L. corniculatus that can be induced by heterogeneous P distribution. The ability to respond to locally increased P availability with enhanced root proliferation has been shown also for many other plant species (Ma and Rengel, 2008;Ma et al, 2007;Kume et al, 2006;Robinson, 1994;Weligama et al, 2007;Denton et al, 2006) in climate chamber experiments, but seldom in the field (Eissenstat and Caldwell, 1988;Buman et al, 1994).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The climate chamber experiment, where all other heterogeneities had been evened out by soil homogenization, confirmed that preferential allocation of root growth is indeed a response of L. corniculatus that can be induced by heterogeneous P distribution. The ability to respond to locally increased P availability with enhanced root proliferation has been shown also for many other plant species (Ma and Rengel, 2008;Ma et al, 2007;Kume et al, 2006;Robinson, 1994;Weligama et al, 2007;Denton et al, 2006) in climate chamber experiments, but seldom in the field (Eissenstat and Caldwell, 1988;Buman et al, 1994).…”
Section: Discussionmentioning
confidence: 97%
“…Laboratory and greenhouse experiments with constructed heterogeneities and/or split root systems have shown that localized P supply can induce preferential root proliferation in many plant species (Kume et al, 2006;Ma and Rengel, 2008;Ma et al, 2007;Robinson, 1994;Weligama et al, 2007;Denton et al, 2006). Some authors also studied preferential root growth in response to localized P fertilization in the field (Eissenstat and Caldwell, 1988;Buman et al, 1994;Caldwell et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…No-till combined with strip fertilization increases the horizontal spatial variation of K in soils (e.g., a higher K concentration on the fertilized sides and a lower K concentration on the unfertilized sides). This spatial variation occurs due to the wide-row spacing, the fixed crop rows and the fertilizer bands, the high crop residue concentration on the crop rows, the differences in soil properties in relation to their position in the crop-row, and limited K mobility in dry land soils ( Ma et al, 2007 ; Farmaha et al, 2011 , 2012 ; FernĂĄndez et al, 2011 , 2015 ; Williams et al, 2017 ). In rainfed systems, such as those of wheat growing areas in Northern China, the horizontal spatial variation of K is more noteworthy since soil drying conditions generally occur at the end of the growing season when K and water are in greatest demand by wheat ( FernĂĄndez et al, 2011 ; Zhao et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…As for other soil resources, there is often remarkable heterogeneity in the spatial distribution of P and water in soil, even within the domain of a single root system (Jackson and Caldwell 1993;Farley and Fitter 1999). Preferential allocation of roots in soil patches or zones with increased P and water availability has been reported for many plant species (Kume et al 2006;Ma et al 2007;Weligama et al 2007;Ma and Rengel 2008). Little is known about growth responses to heterogeneous soil water distribution for plants developing cluster roots, while contrasting findings have been reported for responses of cluster root formation to P heterogeneity.…”
Section: Introductionmentioning
confidence: 99%